2004
DOI: 10.1176/appi.ajp.161.2.242
|View full text |Cite
|
Sign up to set email alerts
|

Partial Recovery of Brain Metabolism in Methamphetamine Abusers After Protracted Abstinence

Abstract: The persistent decreases in striatal metabolism in methamphetamine abusers could reflect long-lasting changes in dopamine cell activity, and decreases in the nucleus accumbens could account for the persistence of amotivation and anhedonia in detoxified methamphetamine abusers. The recovery of thalamic metabolism could reflect adaptation responses to compensate for the dopamine deficits, and the associated improvement in neuropsychological performance further indicates its functional significance. These results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
174
2
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 207 publications
(189 citation statements)
references
References 25 publications
12
174
2
1
Order By: Relevance
“…The extent to which those characterizations can be generalized for interpreting METH's effects on human brain neurochemistry has remained tenuous for many years. Now, as was observed in animal studies, some METHassociated effects on the striatal dopamine (DA) system have also been consistently shown in humans, in vivo, with PET imaging, namely, lower dopamine transporter (DAT) ligand binding (15-30%) (McCann et al, 1998;Sekine et al, 2001;Volkow et al, 2001;Wang et al, 2004;Johanson et al, 2006). A post-mortem study has also shown lower DAT ligand binding, in addition to reductions in DA and tyrosine hydroxylase protein content (Wilson et al, 1996).…”
Section: Introductionmentioning
confidence: 66%
“…The extent to which those characterizations can be generalized for interpreting METH's effects on human brain neurochemistry has remained tenuous for many years. Now, as was observed in animal studies, some METHassociated effects on the striatal dopamine (DA) system have also been consistently shown in humans, in vivo, with PET imaging, namely, lower dopamine transporter (DAT) ligand binding (15-30%) (McCann et al, 1998;Sekine et al, 2001;Volkow et al, 2001;Wang et al, 2004;Johanson et al, 2006). A post-mortem study has also shown lower DAT ligand binding, in addition to reductions in DA and tyrosine hydroxylase protein content (Wilson et al, 1996).…”
Section: Introductionmentioning
confidence: 66%
“…1,6,8,9 ROIs were drawn on the structural MR template provided in SPM2, using MEDx Software (Sensor Systems, Sterling, VA, USA). Bilateral sampling of these regions provided data on activity changes across sessions within 20 ROIs (that is, 40 comparisons).…”
Section: Discussionmentioning
confidence: 99%
“…8 The thalamic, but not the striatal deficits in relative activity, normalized after the first year. 9 Although the first weeks of abstinence from MA abuse are important for retention in treatment, 10 we know of no reports on cerebral metabolic changes during this period. Such effects might have important implications for therapies that involve specific brain circuits, and therefore are the subject of the present report.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The means by which METH leads to CNS damage with cognitive and psychiatric disorders (Cadet et al, 2003;Nordahl et al, 2003) the degree of potential neurochemical and functional recovery from damage (Volkow et al, 2001;Wang et al, 2004) and its interactions with other pathogenic challenges, such as HIV infection (Rippeth et al, 2004) are still relatively unknown. The use of this experimental animal model will enable the study of the chronic effects of METH, as well as therapeutic means for their amelioration.…”
Section: Discussionmentioning
confidence: 99%